2024
DOI: 10.3389/fragi.2023.1304705
|View full text |Cite
|
Sign up to set email alerts
|

A multi-study analysis enables identification of potential microbial features associated with skin aging signs

Tyler Myers,
Amina Bouslimani,
Shi Huang
et al.

Abstract: Introduction: During adulthood, the skin microbiota can be relatively stable if environmental conditions are also stable, yet physiological changes of the skin with age may affect the skin microbiome and its function. The microbiome is an important factor to consider in aging since it constitutes most of the genes that are expressed on the human body. However, severity of specific aging signs (one of the parameters used to measure “apparent” age) and skin surface quality (e.g., texture, hydration, pH, sebum, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…The results of this study confirmed some observations previously made using 16S rRNA sequencing studies [24][25][26]28,30,33,42] or using more recent whole-genome sequencing (WGS) studies [27,31,32]. The study results first confirmed that microbial diversity increases during aging [24][25][26][27][28][29]41], largely contributed by shifting Proteobacteria populations and Actinobacteria [24,[28][29][30] or Lactobacillales [43]. As reported previously on forehead and/or cheeks, we also observed that in older facial wrinkled skin, there is a decrease in Cutibacterium, formerly Propionibacterium [24][25][26][27]29,31,32] and an increase in Corynebacteria [24,29,33], namely a decrease in C. acnes [24,25,27,31,32] and an increase in C. kroppenstedtii [32,33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study confirmed some observations previously made using 16S rRNA sequencing studies [24][25][26]28,30,33,42] or using more recent whole-genome sequencing (WGS) studies [27,31,32]. The study results first confirmed that microbial diversity increases during aging [24][25][26][27][28][29]41], largely contributed by shifting Proteobacteria populations and Actinobacteria [24,[28][29][30] or Lactobacillales [43]. As reported previously on forehead and/or cheeks, we also observed that in older facial wrinkled skin, there is a decrease in Cutibacterium, formerly Propionibacterium [24][25][26][27]29,31,32] and an increase in Corynebacteria [24,29,33], namely a decrease in C. acnes [24,25,27,31,32] and an increase in C. kroppenstedtii [32,33].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study confirmed some observations previously made using 16S rRNA sequencing studies [24][25][26]28,30,33,42] or using more recent whole-genome sequencing (WGS) studies [27,31,32]. The study results first confirmed that microbial diversity increases during aging [24][25][26][27][28][29]41], largely contributed by shifting Proteobacteria populations and Actinobacteria [24,[28][29][30] or Lactobacillales [43].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of special interest was the observation that this enhancement was greater in older volunteers. While the correlations between aging and microbiota diversity and balance are not fully understood, recent research shows, perhaps counterintuitively, higher diversity in older age [18,45,46]. This could be due to accumulated exposure (seeding) to a consequentially accumulating variety of different microbial species over a lifetime.…”
Section: Discussionmentioning
confidence: 99%